ISOLASI, KARAKTERISASI DAN UJI ANTAGONIS BAKTERI SELULOLITIK TERHADAP Phytophthora capsici ASAL TANAMAN LADA (Piper nigrum L.) SECARA IN-VITRO - Khaeruni, Andi; Satrah, Vit Nehru; Mariadi, Mariadi (Jurnal Agroteknos, 2011)
ABSTRACT The Aim of this experiment was obtain cellulolitic bacteria that has antagonistic potential toward P. capsici of   pepper isolated under in-vitro test.   The experiment was begun in isolation and selection of cellulolitic bacteria from soil samples were taken from some location at Southeast Sulawesi. Selected 20 isolates of cellulolitic bacteria examined for its    morphological and physiological characteristics as  well as antagonistic potential toward   P. capsici of pepper isolated under in-vitro test on Potato Dextrose Agar (PDA) medium. The potential antagonistic test was carry out used randomized complete design with three replications to observes the ability of cellulolitic bacteria inhibited mycelium growth of P. capsici on PDA medium. Results showed the selected isolates very divers on morphological characters in  size, pigmentation, shape,  and  elevation of  surface. Physiological character showed  that  out  of  20  isolates,  12  isolates  have  negative  Gram reaction  and  8  isolates    positive  Gram  reaction.  Obtaining  5  isolates  very  strongly,  11 isolates strongly and 4 isolates weak activities on secreted extracellular cellulose enzyme, all of isolates were facultative anaerobe activity.  Further test on antagonistic ability showed that STS15c and STS12c2 isolates are the best isolates to inhibited mycelium growth of P. capsici on PDA medium in potential inhibited were 53.16% and 52.02% respectively. Key words: Cellulolitic bacteria, Phytophthora capsici, antagonistic